The use and dissemination of religious knowledge in antiquity - Hezser, Catherine; Edelman, Diana Vikander (Equinox, 2021)
"This volume investigates for the first time whether and to what extent religious knowledge - e.g., "sacred" narratives, customary practices, legal rules, family traditions, festival observances - was accessible to and known by ordinary people beyond religious functionaries. This book is the first collaborative interdisciplinary study of this important subject area with chapters written by international experts on ancient Mesopotamia, the Hebrew Bible, Qumran literature, rabbinic literature, and early Christianity including apocrypha and monastic traditions"--